INFLUENCE OF PARTICIPATION COMPILATION OF BUDGET TO PERFORMANCE OF MANAJERIAL GOVERNMENTAL APARATUR OF SUB-PROVINCE OF SOLOK WITH ORGANIZATIONAL CULTURE AND ORGANIZATIONAL COMMITMENT AS VARIABLE OF MODERATING - Kardilla, Dessy - (Pendidikan Ekonomi, 2014)
This research aim to to analyse 1) Influence of participation compilation of budget to performance of manajerial governmental aparatur of sub-province of Solok 2) cultural influence of organization to performance of manajerial governmental aparatur of sub-province of Solok 3) influence of organizational komitmen to performance of manajerial governmental aparatur of sub-province of Solok 4) Cultural of organization of memoderasi influence of participation compilation of budget to performance of manajerial governmental aparatur of sub-province of Solok 5) Organizational Komitmen of memoderasi influence of participation compilation of budget to performance of manajerial governmental aparatur of sub-province of Solok.This Research time is conducted in August and September 2014. Research type which is used in this research is quantitative research. This research population is power consumer of budget ( KPA) at SKPD ( set of activity peripheral of area) in governance of sub-province of Solok. Technique intake of sampel with sampling purposive with amount of sampel counted 52 people have the power consumer of budget. Technique analyse data: descriptive analysis and inductive analysis, that is test of normalitas, test heteroskedastisitas, test interaction test and autokorelasi by using Moderated Regression Analysis ( MRA) constructively program of SPSS version 16.0.Result of research indicate that 1) there are influence which are positive and signifikan between influence of participation compilation of budget to performance of manajerial in governmental aparatur of sub-province of Solok 2) there are negative influence and do not signifikan between cultural influence of organization to performance of manajerial 3) there are negative influence and do not signifikan between organizational komitmen to performance of manajerial 4) there are positive influence and do not cultural interaction signifikan of organization at participation compilation of budget to performance of manajerial 3) there are influence which are positive and signifikan between organizational komitmen at participation compilation of budget to performance of manajerial.